Design and development of virtual and augmented reality systems to enhance learning and training in assembly process - Mahmod @ Wahab, Rohidatun (2017)
In various industries and education sector, teaching, learning and training have become very important in order to acquire a new skill, especially in assembly or disassembly (maintenance) operations among users, employees, engineers and technicians. Most of practioners are looking for an alternative learning and training method in order to support their demand to equip the new users with the necessary knowledge and skills based on their current manufacturing processes. Nevertheless, it has become very challenging to train a new worker to efficiently perform new skills, especially for complex, critical or expensive parts of assembly (installation) or disassembly (maintenance). Notably, the requirements for alternative learning and training method are now widely researched and highly demanding, as it is important to effectively reduce user‟s training and working time in order to avoid cost issues related to training, material, experts unavailability and avoid actual part damage. Mistakes made by the learner or trainee using the real components could be devastating and / demoralizing to the learner and harmful to the environment. Therefore, the purpose of this study is to design and develop Virtual Reality (VR) system for training the assembly process, design and develop Augmented Reality (AR) system for learning of the assembly process and evaluate the efficiency of the implementation of learning and training through Augmented Reality (AR) and Virtual Reality (VR) system. The valve assembly system was selected as the task of study for the mechanical assembly process procedure. The development and integration of Virtual Reality (VR) integrated with a Phantom™ Omni-SensAble Technologies OpenHaptics™ toolkit and application of Augmented Reality (AR) system were used including; CATIA, Unity, BLENDER, Augment Software and Augment Apps in a mobile device (iPad Air 2). This study involved and evaluated on the influence of interactive learning method using simulation in the AR system (Augment App) compared with learning using video simulation (desktop); ARVR group compared with the Control ARVR group. The findings of this study indicated that the Task Completion Time (TCT) for ARVR group was better (11.7%) when compared to the Control ARVR group, while the total assembly error was also less (45.57%) for the ARVR group as compared to the Control ARVR group. Based from the results obtained in this study, it can be concluded that, the combination of interactive learning method using AR system (Augment-Apps using iPad) and training in the VR platform were found to be the best method for users in learning a new assembly task according to the positive results of TCT, total assembly error, performance and feedback received. Moreover, the statistical analysis showed that participants had positive feedback using the system and mentioned that it was a good alternative solution for the virtual training process without using the actual parts or components. Therefore, this learning and training platform will be shared among education sectors and the industry players. This may help them for cost optimization (which is reducing training material and avoid using actual component that might be costly) and shortening the training time, while still resulting in a better skill performance. Nowadays, organization and individual can afford to buy and to have a mobile phone for experience learning method through AR application, they also can learn everywhere and anytime they want to study. Therefore, new users are able to perform the expected tasks immediately after the training is completed.